Návrhy strategie řízení podpory prodeje firmy - Viková, Miroslava (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
V diplomová práci analyzuji strategickou pozici předního výrobce energetických nápojů a navrhnout přístupy podporující udržení a zlepšení konkurenčního postavení na trhu. Výsledkem této diplomové práce, by měly být návrhy na zlepšení strategie řízení podpory prodeje firmy Pinelli v oblasti nealkoholických a energetických nápojů. Tyto návrhy by měly být základnou konkurenceschopnosti a zlepšení postavení na trhu.

This thesis deals with analyzing strategic position of energetic drinks production company. It mainly focuses on establishing a way the company can sustain and improve its current competitive position in the market. The results of the analysis in this thesis should be able to come up with measures that can help the company improve its sales promotion strategy in its area of activity – energy drinks. These measures should be the basis for its competitiveness and sustaining its position in the market.
Strategy for Managing Sales Promotion of Company
Keywords: Marketing; marketingová strategie; sponzoring; propagační akce; podpora prodeje; kontrola propagačních akcí; média; marketingová podpora; reklamní předměty; stimuly; Marketing; marketing strategy; sponsorship; promotion action; sales promotions; control of promotion action; media; marketing support; free gifts; stimuli